Artificial keloid skin models: understanding the pathophysiological mechanisms and application in therapeutic studies - Kwon, Soo hyun; Lee, Jongmin; Yoo, Jin; Jung, Youngmee (Royal Society of Chemistry, 2024)
Keloid is a type of scar formed by the overexpression of extracellular matrix substances from fibroblasts following inflammation after trauma. The existing keloid treatment methods include drug injection, surgical intervention, light exposure, cryotherapy, etc. However, these methods have limitations such as recurrence, low treatment efficacy, and side effects. Consequently, studies are being conducted on the treatment of keloids from the perspective of inflammatory mechanisms. In this study, keloid models are created to understand inflammatory mechanisms and explore treatment methods to address them. While previous studies have used animal models with gene mutations, chemical treatments, and keloid tissue transplantation, there are limitations in fully reproducing the characteristics of keloids unique to humans, and ethical issues related to animal welfare pose additional challenges. Consequently, studies are underway to create in vitro artificial skin models to simulate keloid disease and apply them to the development of treatments for skin diseases. In particular, herein, scaffold technologies that implement three-dimensional (3D) full-thickness keloid models are introduced to enhance mechanical properties as well as biological properties of tissues, such as cell proliferation, differentiation, and cellular interactions. It is anticipated that applying these technologies to the production of artificial skin for keloid simulation could contribute to the development of inflammatory keloid treatment techniques in the future. Keloid is a type of scar formed by the overexpression of extracellular matrix substances from fibroblasts following inflammation after trauma.